Three‐dimensional texture of natural pseudotachylyte: Pseudotachylyte formation mechanism in hydrous accretionary complex. (3rd January 2018) - Hamada, Yohei; Kimura, Gaku; Kameda, Jun; Yamaguchi, Asuka; Hamahashi, Mari; Fukuchi, Rina; Kitamura, Yujin; Okamoto, Shin'ya
Abstract: Melt‐origin pseudotachylyte is the most reliable seismogenic fault rock. It is commonly believed that pseudotachylyte generation is rare in the plate subduction zone where interstitial fluids are abundant and can trigger dynamic fault‐weakening mechanisms such as thermal pressurization. Some recent studies, however, have discovered pseudotachylyte‐bearing faults in exhumed ancient accretionary complexes, indicating that frictional melting also occurrs during earthquakes in subduction zones. To clarify the pseudotachylyte generation mechanism and the variation of slip behavior in the plate subduction zone, a pseudotachylyte found in the exhumed fossil accretionary complex (the Shimanto Belt, Nobeoka, Japan) was re‐focused and microscopic and three‐dimensional observations of the pseudotachylyte‐bearing fault were performed based on optical, electron, and X‐ray microscope images. Based on the patterns contained in the fragment, the pseudotachylyte is divided into four domains, although no clear domain boundaries or layering structures are not found. Three‐dimensional observation also suggests that the pseudotachylyte were fragmented or isolated by cataclasite or carbonate breccia. The pseudotachylyte was rather injected into the surrounding carbonate breccia, which is composed of angular fragments of the host rock and a matrix of tiny crystalline carbonate. The pseudotachylyte volume was extracted from the X‐ray microscope image and the heat abundance consumed by the pseudotachylyte generation was estimated at 2.18 MJ/m 2, which can be supplied during a slip of approximately 0.5 m. These observations and calculations, together with the results of the previous investigations, suggest hydrofracturing and rapid carbonate precipitation that preceded or accompanied the frictional melting. Dynamic hydrofracturing during a slip can be caused by rapid fluid pressurization, and can induce abrupt decrease in fluid pressure while drastically enhancing the shear strength of the shear zone. Consequently, frictional heating would be reactivated and generate the pseudotachylyte. These deformation processes can explain pseudotachylyte generation in hydrous faults with the impermeable wall rock. Abstract : This paper deals with the detailed texture of a pseudotachylyte developing in an on‐land fossilized accretionary complex and the pseudotachylyte generation mechanism in hydrous condition. 3‐D micro texture of the pseudotachylyte were described by using optical‐, electron‐ and X‐ray microscope. Based on the description and occurrence of the pseudotachylyte, it is suggested that dynamic decrease of fluid pressure along a fault is necessary for pseudotachylyte generation at seismogenic depth in hydrous plate subduction zone. Abstract : 熔融起源のシュードタキライトは地震の直接的な証拠である. しかし, プレート沈み込み帯などの堆積物中での地震は, 間隙中に含まれる多量の水のために摩擦発熱が生じにくく, シュードタキライトの形成が妨げられると考えられてきた. 本研究では, 四万十帯・延岡衝上断層近傍に発達する堆積物中のシュードタキライトについて, 光学顕微鏡・電子顕微鏡に加えてX線コンピュータ断層撮影を用いた三次元的な観察を行い, その形成過程を議論した. シュードタキライトに層構造は認められず, またシュードタキライトの体積から, 断層のすべり距離は数十センチ以内と見積もられる. 周囲の炭酸塩鉱物脈の産状は, 断層運動時に水圧破砕が生じたことを示しており, シュードタキライトはその水圧破砕の後に生じていたことが明らかとなった. 含水堆積物中でのシュードタキライトの形成には, 断層運動時の摩擦発熱による間隙水圧の上昇を打ち消す作用として水圧破砕が有効に機能する必要がある.